Business Strategy Formulation for Crunchy’s Fried Chicken at Bekasi Area - Tri Moerdani, Laksmana; Toha, Mohamad (The Indonesian Journal of Business Administration, 2013)
The growth of the franchise is growing in Indonesia. The existence of a flourishing franchise in recent years cannot be avoid anymore. Crunchy's Fried Chicken or be referred by CrFC is one of thousands of existing brands. With so many competitors in the market, the products are particularly common in the region causing CrFC to determine the right business strategy formulation to be well received by the market. This study will explore the formulation of business strategy CrFC using a business model. Product leadership and customer intimacy use in crafting the Business strategy formulation.Â Keywords: Crunchy's Fried Chicken, Business Strategy, Business Model Canvas, Customer Intimacy, Product Leadership